Impact of Body Mass Index on the Outcomes of Catheter Ablation of Atrial Fibrillation: A European Observational Multicenter Study. Issue 20 (15th October 2019) - Providência, Rui; Adragão, Pedro; de Asmundis, Carlo; Chun, Julian; Chierchia, Gianbattista; Defaye, Pascal; Anselme, Frédéric; Creta, Antonio; Lambiase, Pier D.; Schmidt, Boris; Chen, Shaojie; Cavaco, Diogo; et al.
Abstract : Background: Outcomes of catheter ablation of atrial fibrillation (AF) are variable and the predictors of success require further elucidation since the identification of correctable risk factors could help to optimize therapy. We aimed to assess the impact of body mass index (BMI) in the overall safety and efficacy of catheter ablation of AF, with emphasis on the use of cryoballoon ablation and novel oral anticoagulants. Methods and Results: There were 2497 consecutive patients undergoing catheter ablation of AF in 7 European high volume centers were stratified according to BMI (normal weight <25 kg/m 2, pre‐obese 25–30 kg/m 2, obesity 30–35 kg/m 2, and morbid obesity ≥35 kg/m 2 ) and comparisons of procedural outcomes evaluated. Pre‐obese and obese patients presented more comorbidities (hypertension, diabetes mellitus, and sleep apnea), and had higher rates of non‐paroxysmal AF ablation procedures. The rate of atrial 12‐month arrhythmia relapse increased alongside with BMI (35.2%, 35.7%, 43.6%, and 48.0% P <0.001). During a median follow‐up of 18.8 months (interquartile range 11–28), after adjusting for all baseline differences, BMI was an independent predictor of relapse (hazard ratio=1.01 per kg/m 2 ; 95% CI 1.01–1.02; P =0.002), adding incremental predictive value to obstructive sleep apnea. BMI was not a predictor for any of the reported complications. Using novel oral anticoagulants and cryoballoon ablation was safe and efficacy was comparable with vitamin‐K antagonists and radiofrequency ablation. Conclusions: Obese patients present with a more adverse comorbidity profile, more advanced forms of AF, and have lower chances of being free from AF relapse after ablation. Use of novel oral anticoagulants and cryoballoon ablation may be an option in this patient group.